The Representation of Africa’s Intangible Heritage in Madagascar Escape 2 Africa (2008) - Gonese, James; Chivandikwa, Nehemiah; Mabasa, Ignatius T (Journal of Cultural Heritage and Development, 2025)
This study explores how the Western animated film Madagascar: Escape 2 Africa (2008) portrays African cultural themes and how intangible aspects are represented. The study employs a qualitative research approach grounded in Critical Discourse Analysis (CDA). The research purposively sampled key scenes that depict African cultural narratives; these scenes were transcribed, taking note of verbal utterances, and visual cues were annotated and thematically coded to identify patterns relating to stereotypes and counter-narratives by focusing on the examination of power dynamics. The key findings reveal a troubling trend of misrepresentation, where African spirituality is often depicted through superstition and inferiority, and oral traditions are wrongly associated with illiteracy. However, the film also offers glimpses of African community values, suggesting that despite prevalent stereotypes, a counter-narrative exists that deserves attention. These findings encourage us to adopt a more nuanced perspective on African representation in media, advocating for self-representation that genuinely reflects the richness and diversity of African cultures.